2022
DOI: 10.3390/nu14050943
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Cutoff Value for Reduced Muscle Mass for GLIM Criteria in Patients with Gastrointestinal and Hepatobiliary–Pancreatic Cancers

Abstract: The Global Leadership Initiative on Malnutrition (GLIM) criteria recommends using race- and sex-adjusted cutoff values for reduced muscle mass (RMM), but the only cutoff values available for Asians are the skeletal muscle mass index (SMI) established by the Asian Working Group for Sarcopenia (AWGS). This retrospective study aimed to develop and validate cutoff values for the fat-free mass index (FFMI) and arm circumference (AC) of Asians, and to investigate the association between GLIM malnutrition and prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…To compare differences in depression indicators among different groups of malnutrition phenotype, the phenotypes were grouped according to the results of previous studies and guidelines. Among the phenotypes associated with decreased muscle mass, upper arm circumference (AC) cutoffs were <27 cm in men and <25 cm in women ( 17 ). and calf circumference (CC) cutoff was <33 cm in men and <32 cm in women ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…To compare differences in depression indicators among different groups of malnutrition phenotype, the phenotypes were grouped according to the results of previous studies and guidelines. Among the phenotypes associated with decreased muscle mass, upper arm circumference (AC) cutoffs were <27 cm in men and <25 cm in women ( 17 ). and calf circumference (CC) cutoff was <33 cm in men and <32 cm in women ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported the association between GLIM-defined malnutrition and survival [21][22][23]. The GLIM criteria have been validated for pancreatic cancer as well [24].…”
Section: Assessment Of Nutritional Statusmentioning
confidence: 99%
“…WLP might be effective for early stage gastrointestinal surgery; however, its influence on patients with HCC remains unknown. In our institution, nutritional assessment prior to digestive surgery is well established [12, 13], and malnutrition has been reported to lead to poor prognosis after gastrointestinal and hepatobiliary–pancreatic surgery [14]. Therefore, interventions for malnutrition (including high BMI) are critical in digestive surgery.…”
Section: Introductionmentioning
confidence: 99%